2016
DOI: 10.1093/ajcp/aqw105
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Genetic Testing Order Errors With a Laboratory Utilization Management Program

Abstract: Clinicians without specialty training in genetics make genetic test order errors at a significantly higher rate than geneticists. A laboratory utilization management program prevents these order errors from becoming diagnostic errors and reaching the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…We found that tests were ordered by both obstetrician gynecologists and certified midwives functioning as perinatal providers, infertility sub‐specialists, and primary care providers such as family practice physicians. Previous studies have identified higher errors for genetic tests ordered by providers without specialty training in genetics (Mathias et al., 2016). We also found cases where a screening test was initially ordered with a family history of cancer, followed by the addition of targeted testing based on genetic studies of the affected individual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that tests were ordered by both obstetrician gynecologists and certified midwives functioning as perinatal providers, infertility sub‐specialists, and primary care providers such as family practice physicians. Previous studies have identified higher errors for genetic tests ordered by providers without specialty training in genetics (Mathias et al., 2016). We also found cases where a screening test was initially ordered with a family history of cancer, followed by the addition of targeted testing based on genetic studies of the affected individual.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study are the thorough review of ordered genetic tests and the chart review to determine the appropriateness of testing. (Mathias et al, 2016), and other techniques including order restriction and guidance (Dickerson et al, 2014…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Misutilization—the ordering of laboratory tests that are inappropriate for the clinical questions being asked—is fostered by the ever-increasing number of available laboratory tests and the inability of busy physicians to stay abreast of their utility. 56,70 -72 Indeed, a resolution was recently passed by the House of Delegates of the American Medical Association to close potential gaps in the training of physicians in use and interpretation of laboratory tests. 73 The following case illustrates the seriousness of this issue.…”
Section: Reducing Diagnostic Errorsmentioning
confidence: 99%
“…A specific intervention that enhances teamwork is the implementation of diagnostic management teams in any of the areas where they have shown to be effective including coagulopathy and hematologic malignancy (5). Another teamwork intervention is the review of complex genetic test orders by a genetic counselor, especially if ordered by a physician who is not a geneticist (6)(7)(8). This addresses the nearly one-third of genetic tests orders that contain errors.…”
mentioning
confidence: 99%